Competitiveness and Processing of Processed Cocoa Industry in Improving the Welfare of People’s Cocoa Farmers in East Java - Gyska Indah Harya; Sudiyarto; Gideon Setya Budiwitjaksono; Markus Patiung (Future Science)
This study aims to explain and explore government policies and the competitiveness of processed cocoa to the welfare of cocoa farmers in East Java. The research method uses quantitative descriptive analysis with the Revealed Comparative Advantage (RCA) method, and the approach of the Minister of Agriculture of the Republic of Indonesia Number: 67 / Permentan / ot.140 / 5/2014 concerning the quality and marketing of cocoa beans. The population of this research is Smallholder Cocoa Farmers in 9 regions of East Java with 45 respondents through indicators: the performance of cocoa farming, cocoa farming income in meeting the needs of spending on the production of facilities and infrastructure for cocoa farming, basic expenditure, education, social, communication, recreation, transportation, home care, and health costs. The results showed that the comparative advantage of East Java cocoa based on the results of the calculation of competitiveness (RCA), for processed cocoa commodities valued> 1 in 2015 - 2017 which means that processed products of East Java have competitiveness, then in 2018 the results of the RCA showed a value < 1, which means that East Java processed cocoa products do not yet have competitiveness in the national market. Through the Government Policy approach (Permentan no: 67 / Permentan / ot.140 / 5/2014) shows that all cocoa farmers in Blitar, Mojokerto, Trenggalek, Ponorogo, Pacitan have implemented cocoa cultivation following the implementation of cocoa post-harvest handling guidelines. Whereas in Malang, Nganjuk, Madiun, Jombang regencies have not consistently applied guidelines for handling post-harvest cocoa. The level of welfare of cocoa farmers shows that Blitar, Mojokerto, Trenggalek, Ponorogo, Pacitan districts consistently have a high level of welfare compared to Malang, Nganjuk, Madiun, Jombang districts that have not consistently improved the welfare of Cocoa farmers.